Effect of micro-nutrients spray on quality attributes of mango (Mangifera indica L.) cv. Amrapalli (Indian Journal of Arid Horticulture, 2016)
The mango occupies a pre-eminent place amongst the fruit crops grown in India as the king of fruits. Belonging to the family Anacardiaceae, the mango (Mangifera indica L.) is the fifth most important fruit in the world after apple, citrus, banana, and grape. It is cultivated in more than 100 countries due to its delicious taste, excellent flavor, attractive fragrance, and as an excellent source of vitamins A and C. Mango occupies about 70 percent of the total area under fruits in India, covering 5.51 million hectares. Major mango-producing countries include India (12.53 million tonnes), China (3.67 million tonnes), Mexico (1.67 million tonnes), Thailand (1.80 million tonnes), Pakistan (16.06 million tonnes), Indonesia (1.14 million tonnes), and the Philippines (1.003 million tonnes). India’s share in world mango production was 40.1% as of 2009, a figure that has not substantially increased since then. The total annual mango production in India is estimated at 16.07 million tonnes from 2.4 million hectares (2010-11). All parts of the mango plant have various uses. Both ripe and unripe mangoes are extensively used by the food processing industry to prepare a wide variety of products, such as syrup, jam, squash, juice, cereal flakes, and toffee. Ripe mangoes are also used to make pickles, chutney, slices, amchur, candy, jam, jelly, and preserves from unripe mangoes. The chemical composition of mango varies with the variety and stage of maturity. It is a rich source of carbohydrates as well as vitamins A and C. A comprehensive report has been made on the chemical composition after analyzing more than five varieties of mango, such as Fazli, Chausa, Langra, and Dasheri. Mango is one of the best-exported materials both in fresh and processed forms and is exported to countries including the U.K., U.S.A., France, Kuwait, Bahrain, Afghanistan, Malaysia, Qatar, and Singapore.
Keywords: Singapore; Afghanistan; Fazli